Assessment of Back‐End‐of‐Line Compatibility of Sputtered HfO2‐Based Ferroelectrics. Issue 10 (27th January 2022) - Wang, Xuetao; Mikolajick, Thomas; Grube, Matthias
Abstract : The thermal compatibility of fully sputtered, ferroelectric TiN/Hf x Zr(1− x ) O2 /TiN thin‐film capacitors with back‐end‐of‐line processing is investigated. The sputtering power, ZrO2 concentration, and annealing temperature affect the crystal structure and ferroelectric properties of Hf x Zr(1− x ) O2 (HZO) in different ways, which is revealed by the grazing incidence X‐ray diffraction and electric characterization. Moderate sputtering power and ZrO2 content favor the orthorhombic phase and higher remanent polarization. In contrast, low and high power or low and high ZrO2 concentrations increase the monoclinic and tetragonal/cubic phase fractions, respectively. For the first time, it is shown that annealing at 400 °C for 1 h can result in fully crystalline HZO films deposited by physical vapor deposition. Even pure HfO2 deposited from a 3 in. target with a sputtering power of 50 W exhibits some ferroelectric response after annealing at 400 °C and wakeup cycling. Abstract : The thermal compatibility with back‐end‐of‐line (BEOL) processing of fully sputtered, ferroelectric TiN/Hf x Zr(1− x ) O2 /TiN capacitors is investigated. Varying sputtering power, ZrO2 concentration, and annealing temperature can modify the crystal phase of the Hf x Zr(1− x ) O2 ( HZO) . BEOL‐like annealing (400 °C for 1 h) can fully crystallize such system and stimulate proper ferroelectricity when applying the correct sputtering parameters.